Cross-sectional study to investigate the presence of sarcopenic dysphagia in a Portuguese geriatric population - Portinha, Susana (2021)
Oropharyngeal Dysphagia (OD) and sarcopenia have been recognized as geriatric syndromes and have shown a higher prevalence in institutionalized elderly, being associated with increased socioeconomic burdens. The objectives were to investigate the presence of sarcopenia and risk of OD in a geriatric population and to analyse the relationship between the factors associated with Sarcopenic Dysphagia (SOD). We have observed that female gender, low educational level and score ≥4 on the SARC-F screening test are associated with higher odds of being at risk for OD, sarcopenia, and even probable SOD. Based on the results, we suggested including a Speech and Language Therapist in the multidisciplinary geriatric teams in order to improve the prevention of OD, sarcopenia and SOD, avoiding its consequences.